2015
DOI: 10.1016/s2352-3018(15)00200-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence, and associated risk factors of tuberculosis in children with HIV living in the UK and Ireland (CHIPS): a cohort study

Abstract: NHS England, PENTA Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
8
2
3
Order By: Relevance
“…This study showed that the incidence of TB was higher among WHO clinical stages 3 and 4 compared to 1 and 2. This finding was in agreement with those of studies done in Tanzania [24], China [20], UK, and Ireland [32]. The declining of immunity in advanced WHO clinical stages accelerates the progression of latent TB infection to active TB infection so that children presenting with advanced WHO clinical stages need to have close monitoring.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed that the incidence of TB was higher among WHO clinical stages 3 and 4 compared to 1 and 2. This finding was in agreement with those of studies done in Tanzania [24], China [20], UK, and Ireland [32]. The declining of immunity in advanced WHO clinical stages accelerates the progression of latent TB infection to active TB infection so that children presenting with advanced WHO clinical stages need to have close monitoring.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, TB incidence rate of this study was higher than that of a study conducted in Latin America [16], UK and Ireland [32], and China [20]. This variation might be due to the fact that the incidence rate of TB was low in the general population of high-income countries.…”
Section: Discussioncontrasting
confidence: 74%
“…Even with cART, comorbidity incidence (including tuberculosis, childhood infections and malignancies) is higher in HIV-infected than uninfected children [87,88,89,90,91]; infections still predominate as causes of death [21,22,92,93]. AIDS-defining infections have declined, but non-AIDS defining conditions (sepsis; pneumonia) remain relatively stable [21,22,92,93,94].…”
Section: Comorbidities That Reduce Survival In Hiv-infected Childrenmentioning
confidence: 99%
“…With paediatric HIV cases also increasing globally, the burden to prevent the disease is increasing 9. The patient was tested for HIV to check for any association but test result was negative.…”
Section: Discussionmentioning
confidence: 99%